Deubiquitinating enzyme USP2 regulates brown adipose tissue thermogenesis via controlling EBF2 stabilization - Yuejie Xu; Ying Chen; Ningning Bai; Yingying Su; Yafen Ye; Rong Zhang; Ying Yang; Caizhi Liu; Cheng Hu; Jiemin Pan (Molecular Metabolism)
Objective: The activation of brown adipose tissue (BAT) promotes energy expenditure is recognized as a promising therapeutic strategy for combating obesity. The deubiquitinating enzyme family members are widely involved in the process of energy metabolism. However, the specific deubiquitinating enzyme member that affects the BAT thermogenesis remains largely unexplored. Methods: Adeno-associated virus, lentivirus and small molecule inhibitor were applied to generate USP2 gain- or loss-of-function both in vivo and in vitro. OxyMax comprehensive laboratory animal monitoring system, seahorse and transmission electron microscopy were used to determine the energy metabolism. Quantitative proteomics, immunofluorescence staining and co-immunoprecipitation were performed to reveal the potential substrates of USP2. Results: USP2 is upregulated upon thermogenic activation in adipose, and has a close correlation with UCP1 mRNA levels in human adipose tissue. BAT-specific Usp2 knockdown or systemic USP2 inhibition resulted in impaired thermogenic programs both in vivo and in vitro. Conversely, overexpression of Usp2 in BAT conferred protection against high-fat diet-induced obesity and associated metabolic disorders. Proteome-wide analysis identified EBF2 as the substrate of USP2 that mediates the thermogenic function of USP2 in BAT. Conclusions: Our data demonstrated the vital role of USP2 in regulating BAT activation and systemic energy homeostasis. Activation of USP2-EBF2 interaction could be a potential therapeutic strategy against obesity.